Heat shock protein 90 inhibitors in the treatment of cancer: current status and future directions. (May 2014) - Jhaveri, Komal; Ochiana, Stefan O; Dunphy, Mark PS; Gerecitano, John F; Corben, Adriana D; Peter, Radu I; Janjigian, Yelena Y; Gomes-DaGama, Erica M; Koren, John; Modi, Shanu; Chiosis, Gabriela
<x xml:space="preserve">Abstract</x> Introduction: Heat shock protein 90 (HSP90) serves as a critical facilitator for oncogene addiction. There has been augmenting enthusiasm in pursuing HSP90 as an anticancer strategy. In fact, since the initial serendipitous discovery that geldanamycin (GM) inhibits HSP90, the field has rapidly moved from proof-of-concept clinical studies with GM derivatives to novel second-generation inhibitors. Areas covered: The authors highlight the current status of the second-generation HSP90 inhibitors in clinical development. Herein, the authors note the lessons learned from the completed clinical trials of first- and second-generation inhibitors and describe various assays attempting to serve for a more rational implementation of these agents to cancer treatment. Finally, the authors discuss the future perspectives for this promising class of agents. Expert opinion: The knowledge gained thus far provides perhaps only a glimpse at the potential of HSP90 for which there is still much work to be done. Lessons from the clinical trials suggest that HSP90 therapy would advance at a faster pace if patient selection and tumor pharmacokinetics of these drugs were better understood and applied to their clinical development. It is also evident that combining HSP90 inhibitors with other potent anticancer therapies holds great promise not only due to synergistic antitumor activity but also due to the potential of prolonging or preventing the development of drug resistance.